EFFECT OF DIFFERENT LEVELS OF LICORICE ROOTS POWDER TO DIETS ON PRODUCTIVE PERFORMANCE AND SOME BLOOD TRAITS FOR QUAIL - Khalid Hadi Mustafa Al-Sofee (Mesopotamia Journal of Agriculture)
This study was conducted in the Poultry farm of Animal Resources Dept., College of Agric. & Forestry, Mosul Uni., in order to investigate the effect of different levels of licorice roots powder to diets on productive performance and some blood traits for quail. Two hundred fifty six unsexed quail (Coturnix coturnix) one week old were randomly distributed into four treatments (64 birds/ treatment) with 8 replicates, in each replicate eight birds, and the treatments continued till the age of 42 days of age. The treatments were as follows: 1st (control): reared on the standard ration  without  addition of crushed licorice root, and the 2nd, 3rd and 4th treatments reared on the standard ration supplemented with (0.5,1,1.5)% of crushed licorice root/kg ration respectively. Ration and water were ad libitum along duration of the study. Statistical analysis of data showed no significant differences (p≤0.05) in final body weight, average total weight gain, relative growth rate, total feed consumption, feed conversion ratio, production index, total mortality, dressing percentage also on mainly cuts and secondary cuts, PCV, serum glucose and triglycerides. While the results showed a significant increase in serum total protein in the 2nd and 4th treatments, as well as a significant decrease in the serum cholesterol levels in the 3rd and 4th treatments compared with control (p≤0.05).